Efectos jurídicos de la falta de tipicidad del incesto en hijas menores adultas en el código orgánico integral penal ecuatoriano. Estudio en la ciudad de Machala en el periodo 2013-2014. - Andrade Añazco, Pavel Mijail (2014)
In this research, it has defended the hypothesis that the lack of criminality of incest adult daughters under the Comprehensive Organic Ecuadorian Criminal Code , impunity causes a perfectly attributable conduct and the damage and psychological and social effects that are generated reach minimal relevance to be criminally discussed ; in addition to those he excelled and demonstrated that fundamental rights injured by the incestuous behavior of a father with his youngest daughter adult , infringe the rights of the latter to free development of his personality , the right to have a family and family life , right to health "to live and develop in a stable and nurturing environment that will enable them proper emotional development"; right to sexual freedom and thus harms their right to form a life .